Cross-sectional study of personal protective equipment use, training and biosafety preparedness among healthcare workers during the first months of the SARS-CoV-2 pandemic in Brazil - Kerstin Muner; Julia Kilgour; Tatiana Ometto; Ana Pérola Drulla Brandão; Andrea Pires dos Santos; Ana Marcia Sá Guimarães (BMJ Public Health)
Objectives Brazil has high rates of COVID-19 and tuberculosis among healthcare workers (HCWs). Personal protective equipment (PPE) is essential for their protection. We aimed to evaluate PPE use, training, and preparedness among HCWs in the early months of the SARS-CoV-2 pandemic in Brazil.Methods A cross-sectional study was performed using questionnaires available to HCWs through a website created to provide PPE guidelines. χ2 test and robust Poisson regression identified factors associated with HCWs treating COVID-19 patients (TCOVID-19), lack of training on PPE use and N95 respirator reuse. The speech content of open-ended questions was analysed.Results We analysed 1410 questionnaires collected from April to July 2020 representing 526 Brazilian cities. HCWs-TCOVID-19 had fewer years of work experience, were more likely to reuse PPE, and reported higher stress levels and lower biosafety at the workplace than HCWs not TCOVID-19 patients. Fearful concerns, limited PPE access and pandemic unpreparedness were common among HCWs. Lack of PPE training was associated with the profession and no N95 respirator fit tests. N95 reuse during the pandemic, common to 78% of the HCWs, was associated with the reuse of PPE during the pandemic and reuse of N95 before the pandemic.Conclusions We report the unpreparedness of HCWs and institutions to handle the pandemic, with low rates of training and N95 respirator fit testing and high PPE reuse. N95 reuse was a pre-established practice. This chronic unpreparedness to deal with airborne pathogens may have contributed to one of the highest global rates of tuberculosis and COVID-19 among HCWs.